ECO GREEN PARK BATU - Linda Ayu Wibriana (Manajemen Bisnis, 2014)
This study is based on the importance of service quality on the company. This meant that all the goods and services offered will have a good place in the eyes of the public as consumers and potential consumers. Although relatively new company, but the importance of service quality mak  the company is trying to get customers as possible by providing services and facilities.  The purpose of this study is to analyze quality of service in the Physical dimension (Tangible), reliability, Responsiveness, Assurance, and Empathy on ECO Green Park Batu city. The population in this study are visitor. Total sample of 100 people, with a quota sampling technique and using a questionnaire for data collection. Analyses data using frequency distribution and analysis tools using servqual and Cartesian diagram. The results showed that the A quadrant is a main priority of the counter clerk service providing quickly. Kuadran B or maintain achievement, factors that include the access road to the Park is easy, has a large parking lot, the company providing the information right, the right service / satisfaction of the officer, the company provide information in a clear, swift cleaning service clean the tourist area, safety guard officers ready to serve. Quadrant C or low priority that the appropriate services / satisfaction of the officer, the officer has a vast knowledge when they explain to visitors officials are consistently polite, serving officers earnestly and wholeheartedly, giving service to all visitors without picky, ease of conveying suggestions / complaints. Quadrant D or excessive such factors which include building which attractive, employees have a neat appearance, complete public facilities, reliable officer in operating a vehicle. Seeing this is not a problem if the company providing the service excessively, because it feels it is able to make visitors feel satisfied.  Keywords: Quality of Service, tangible, in tangible